Lymph node yield, depth of invasion, and survival in node-negative oral cavity cancer. (November 2019) - Zenga, Joseph; Divi, Vasu; Stadler, Michael; Massey, Becky; Campbell, Bruce; Shukla, Monica; Awan, Musaddiq; Schultz, Christopher J.; Shreenivas, Aditya; Wong, Stuart; Jackson, Ryan S.; Pipkorn, Patrick
Highlights: For oral cancer, elective neck dissection with 18 or more nodes improves survival. Improved survival was found in thick (depth ≥4 mm) and thin (depth <4 mm) tumors. Elective neck dissection with less than 18 nodes did not improve survival. Abstract: Objective: To determine the effects of nodal yield on survival in early stage oral cavity squamous cell carcinoma (OCSCC) in the context of primary tumor depth of invasion (DOI). Materials and methods: Patients with early-stage clinically node-negative OCSCC who underwent upfront surgery at the primary site were identified using the National Cancer Database between 2004 and 2015. Results: There were 3384 patients with <4 mm DOI and 1387 patients with ≥4 mm DOI identified. Management of the neck included observation (40%), END with <18 nodes harvested ± postoperative radiation (ND < 18, 16%), and END with ≥18 nodes harvest ± postoperative radiation (ND ≥ 18, 44%). When adjusted for relevant covariates, ND ≥ 18 demonstrated statistically significant improvements in overall survival for both DOI < 4 mm and ≥4 mm (DOI < 4 mm: HR 0.67, 95%CI 0.54–0.85; DOI ≥ 4 mm: HR 0.47, 95%CI 0.34–0.64). However, ND < 18 showed no significant difference from observation of the neck regardless of DOI (DOI < 4 mm: HR 0.82, 95%CI 0.63–1.07; DOI ≥ 4 mm: HR 0.72, 95%CI 0.51–1.03). Of patients undergoing END, the most significant factors associated with obtaining a nodal yield of 18 or more were age less than 40 years (HR 2.58, 95%CI 1.84–3.63) and treatment at an academic facility (HR 2.47, 95%CI 2.06–2.96). Conclusions: END with 18 or more nodes is associated with improved survival outcomes in patients with early stage OCSCC regardless of DOI. END with less than 18 nodes, however, does not appear significantly different than observation of the neck alone. Achieving a lymph node yield of 18 or more is multifactorial and includes both patient and provider factors.